Sequías y prensa regional en la cuenca del río Muga (Girona) - Bayés Bruñol, Carles; Ribas Palom, Anna; Saurí Pujol, David (Geographicalia, 2016)
The almost continuous succesion of critical periods of water shortage sin the La Muga river basin supports the definition of droughts as natural hazards increasingly caused by human activities. In this paper we offer a territorial survey of droughts in the La Muga basin drawn from local media sources and with the objective of assessing the spatial and temporal extent of water crises from 1950 to 2001. We also use the local press to identify conflict situations regarding water availability and use, water quality, and ecosystem health, and to interpret management options adressed at solving these conflicts.
Keywords: Drought; water shortages; regional press; Muga river; Catalonia; water management